Behaviour of concrete-filled cold-formed high strength steel circular stub columns. (December 2020) - Su, Meini; Cai, Yancheng; Chen, Xuerui; Young, Ben
Abstract: This paper presents the experimental and numerical investigations of concrete-filled cold-formed high strength steel (CFHSS) circular stub columns. Firstly, a series of tests was conducted on CFHSS circular tubular sections infilled with three different concrete grades, i.e., C40, C80 and C120. The CFHSS circular tubular sections had the nominal 0.2% proof stress (yield stress) up to 1100 MPa. The test specimens were subjected to uniform axial compression The ultimate loads and failure modes of the specimens were obtained and reported in this paper. Secondly, an extensive numerical study accounting for the confinement effect, as well as the non-linearities of materials, geometry and contacts was performed. Upon validation against the test results, a parametric investigation was conducted. A wide range of the cross-section dimensions and section slenderness of CFHSS circular tubular sections infilled with different grades of concrete were considered. The structural behaviour of concrete-filled CFHSS stub columns was investigated, including the ultimate load, end shortening, strength enhancement index and ductility index. Finally, the experimental and numerical results were used to assess the suitability of the design equations specified in the existing American Specifications (AISC and ACI), European Code (EC4) and Japanese Code (AIJ) for the compressive strength of the concrete-filled CFHSS circular stub columns. It was found that the predictions from the existing international design specifications were generally conservative, except for EC4. The predictions by the AIJ are the least conservative and least scattered. However, by using the effective section area of steel tubes for slender cross sections, EC4 provided the most accurate and consistent predictions than the other design specifications. Highlights: Concrete-filled cold-formed high strength steel (CFHSS) circular stub columns were tested. A validated nonlinear FEM was developed, followed by an extensive parametric study. Structural behaviour of the concrete-filled CFHSS circular stub columns was investigated. Effects of parameters on the stub column behaviour were examined and discussed. Current design rules specified in the international specifications were assessed.